2018
DOI: 10.4103/wjnm.wjnm_43_17
|View full text |Cite
|
Sign up to set email alerts
|

Higher event rate in patients with high-risk Duke Treadmill Score despite normal exercise-gated myocardial perfusion imaging

Abstract: This prospective study was carried out to find the negative predictive value of various Duke Treadmill Scores (DTSs) in patients with normal myocardial perfusion imaging (MPI). This study was conducted from August 2012 to July 2015, and 603 patients having normal exercise MPIs were included. Patients were followed for 2 years for fatal myocardial infarction (FMI) and nonfatal myocardial infarction (NFMI). Follow-up was not available in 23 patients, leaving a cohort of 583 participants. DTS was low risk (≥5) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
3
0
4
Order By: Relevance
“…7 Duke Treadmill score is an important predictor of CAD 8,9 as well as the prognosis 10 . Zaman M et al 11 This finding reinforces the regional as well as ethnic differences in the trends of CAD and its risk factors. Another important inference from our results was that there was a significantly different prevalence of obstructive CAD in the patients who had typical symptoms of angina pectoris as compared to the ones who presented with atypical symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…7 Duke Treadmill score is an important predictor of CAD 8,9 as well as the prognosis 10 . Zaman M et al 11 This finding reinforces the regional as well as ethnic differences in the trends of CAD and its risk factors. Another important inference from our results was that there was a significantly different prevalence of obstructive CAD in the patients who had typical symptoms of angina pectoris as compared to the ones who presented with atypical symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…We found high cardiac risk even with low SSS. Previous studies have shown that patients even with normal MPI occasionally had some cardiac risk [8,9]. One reason might be the fact that MPI cannot detect perfusion abnormality when it is distributed equally as seen in balanced ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…After the test, the Duke treadmill score (DTS) was calculated using the exercise time, ST deviation, and angina class [17]. The DTS was grouped into low-risk (with a score of ≥+5), moderate-risk (with scores ranging from −10 to +4), and high-risk (with a score of ≤−11) categories.…”
Section: Exercise Ecg Testmentioning
confidence: 99%